(untitled) (Ameghiniana, 2013)
"A new Middle-Upper Cenomaniam ammonites and dinoflagellates assemblage is described from Víllar Fabre Bay, James Ross Island. The fossil association comprises the following species: Calycoceras (Newboldiceras) cf. planecosta (Kossmat) y Pseudocalycoceras? aff. iudaicum. (Taubenhaus ) (Ammonites) and Diconodinium cristaium, Odontochitina operculata, Oligosphaeridiurn dioiduum, Cribroperidinium edwarsii, Cleistosphaeridium ancorijerum, Cyclonephelium membraniphorum, Pterodinium cingulatum subsp. cingulatum, Oligosphaeridium pulcherrimum; Isabelidinium acuminatum, Canninginopsis denticulata and Endoceratium loodbrokiae (Dinoílagellates ). These Cenomanian fossils -not previously recorded in Antarctica- allow to amend the Campanian age traditionally assigned to the sequences of ViIlar Fabre and Obelisco Bays. In relation to this change, the classification of the previously reported Submortoniceras chicoense (Trask) is revised, concluding that the specimens supposed to be this Campanian ammonites, actualIy belongs partly to Calycoceras (N.) cf. pkmecosta and partly to acanthoceratids ammonites, probably of the genus Eucalucoceras Spath. The stratigraphic relations of the Cenomanian beds of Villar Fabre Bay are analized also in connection with the Lower Cretaceous and Senonian beds of the western margin of James Ross Island."